(untitled) (Journal of Biomedical Sciences, 2015)
The internal thoracic artery (ITA) is the largest artery of the thoracic wall. ITA has become a conduit of choice for coronary artery bypass graft surgery because of its predictable intrathoracic course, anatomical proximity to the heart and excellent long-term patency. The rare and unexpected occurrence of anomalies of the internal thoracic artery such as the one reported here may complicate the entire procedure of revascularization of the myocardium. We conclude that knowledge of variation of internal thoracic artery is necessary during surgical procedures that involve thoracic region. DOI: http://dx.doi.org/10.3126/jbs.v2i1.13032 Journal of Biomedical Sciences 2015 Mar.; 2(1): 7-9